2023
DOI: 10.3847/2041-8213/acc84a
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Collisionless Shocks in Inhomogeneous Magnetized Plasmas

Abstract: Relativistic collisionless shocks are associated with efficient particle acceleration when propagating into weakly magnetized homogeneous media; as the magnetization increases, particle acceleration becomes suppressed. We demonstrate that this changes when the upstream carries kinetic-scale inhomogeneities, as is often the case in astrophysical environments. We use fully kinetic simulations to study relativistic perpendicular shocks in magnetized pair plasmas interacting with upstream density perturbations. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…Reflected particles reach at most 12λ si ahead of the shock front, and the extent of the shock foot is the same for homogeneous and turbulent upstream plasma. We do not observe any of the shock distortions that were seen in previous hybrid and kinetic simulations (e.g., Nakanotani et al 2022;Demidem et al 2023). There the density structures were much larger than the shock width, whereas here the largest density clumps are roughly 3λ si and considerably smaller than the width of the shock transition of about 15λ si .…”
Section: Global Shock Structurecontrasting
confidence: 56%
See 1 more Smart Citation
“…Reflected particles reach at most 12λ si ahead of the shock front, and the extent of the shock foot is the same for homogeneous and turbulent upstream plasma. We do not observe any of the shock distortions that were seen in previous hybrid and kinetic simulations (e.g., Nakanotani et al 2022;Demidem et al 2023). There the density structures were much larger than the shock width, whereas here the largest density clumps are roughly 3λ si and considerably smaller than the width of the shock transition of about 15λ si .…”
Section: Global Shock Structurecontrasting
confidence: 56%
“…So far, the first attempts to investigate the effects of a nonhomogeneous medium on plasma shocks via kinetic simulations have been made for relativistic shocks propagating in pair plasmas. Static large-scale variations of the upstream density significantly modify the conditions of the downstream plasma (Tomita et al 2019) and corrugate the shock front, which leads to efficient particle acceleration (Demidem et al 2023). With a more realistic setup, in which the upstream plasma contains turbulence instead of static density structures, Bresci et al (2023) confirmed an increased efficiency of acceleration at relativistic shocks in the case of strong electromagnetic fluctuations.…”
Section: Introductionmentioning
confidence: 84%
“…We consider a relativistic shock propagating in an inhomogeneous medium. For nonrelativistic or mildly relativistic shocks, it is shown that the interaction between the shock and a shock-upstream denser region can drive the strong magnetic turbulence in the shockdownstream region (Giacalone & Jokipii 2007;Inoue et al 2011;Fraschetti 2013;Mizuno et al 2014;Ohira 2016aOhira , 2016bSlavin et al 2017;Romansky et al 2020;Hu et al 2022;Bresci et al 2023;Demidem et al 2023;Fulat et al 2023). Although there are few studies about a generation of downstream magnetic turbulence in the case of the relativistic shock (Sironi & Goodman 2007;Goodman & Macfadyen 2008;Tomita et al 2022), none of them demonstrate the generation of the magnetic field turbulence that can accelerate CRs rapidly and explain emissions from GRBs.…”
Section: Introductionmentioning
confidence: 99%